No Survival Benefit When Adding Everolimus to Trastuzumab and Paclitaxel in Advanced HER2-Positive BC - Parry, Nicola (MD Conference Express, 2014)
The BOLERO-1 phase 3 clinical trial demonstrated that adding everolimus to weekly trastuzumab and paclitaxel, as first-line therapy, did not improve progression-free survival in women with previously untreated human epidermal growth factor receptor-2-positive advanced breast cancer. PFS was increased by 7 months with everolimus therapy in the HR-negative subgroup; however, this did not cross the statistical significance threshold. Increased adverse events were also reported in the everolimus-treated group, as well as on treatment, AE-related deaths.